The impact of the pediatric transplant on the family: a review of the literature - Mendes, Ana Márcia Chiaradia; Matheus, Maria Clara Cassuli; Bousso, Regina Szylit (Brazilian Journal of Transplantation, 2007)
This study aimed to explore the available knowledge in the scientific literature regarding the experience of families of children who are transplant recipients, and to identify gaps in that area of knowledge. A systematic review of the literature was performed by searching in the Medline, Pubmed and Lilacs database using the keywords child, transplantation and family. Nine texts were selected to the analysis, which were organized in terms of type of study, year and country of origin, purposes, methodological steps, and results. Data analysis allowed the identification of four main categories that have been discussed in the literature: Functioning and Psychosocial adaptation, family experience, quality of life, prognostic indicators; every selected article had been published in foreign countries. In terms of conclusion, it was established that the literature researched already shows solid data proving the great impact that the transplant experience has on the child and the family. However, future research focusing the experience of the family in terms of its functioning within the transplant experience and the Nursing intervention approach focused in these families, is imperative.